Identify The Factors Causing Cost Overrun in Waringin Group Office Projects - Febriansyah, Firman; Caroline, Jenny (Journal of Civil Engineering, Planning and Design, 2023)
Infrastructure development in this globalization era has increased rapidly in line with the need for residential space, businesses, and buildings. Building construction projects have limitations, including cost limits or cost overruns. The conditions of proper use that are less efficient due to the development plan’s location can lead to several risks during construction work. This study aims to identify and analyze the factors influencing cost overruns and determine the most dominant causal factor in cost overruns. By giving questionnaires to 40 respondents, the data were collected and then treated for validity, reliability, normality, and statistical tests through SPSS software. The analysis of the data tested indicated that all variables were declared valid because the results of the correlation between the respondents' answers to each question item obtained a significant value, namely rcount rtable. The reliability test showed that the Cronbach alpha value of all variables was above 0.600. In conclusion, it was very reliable and could be trusted to be used as a variable measuring tool. The most dominant factors causing cost overruns in the Office Waringin Group project consisted of new work items at a mean of 4.33.